Wide Binaries with White Dwarf or Neutron Star Companions Discovered from Gaia DR3 and LAMOST - Zhao, Xinlin; Mu, Huijun; Wang, Song; Li, Xue; Liu, Junhui; Huang, Bowen; Gu, Weimin; Wang, Junfeng; Yi, Tuan; Zhang, Zhixiang; Yuan, Haibo; Bai, Zhongrui; et al. (The Astrophysical journal, 2024)
The Gaia Data Release 3 (DR3) mission has identified and provided about 440,000 binary systems with orbital solutions, offering a valuable resource for searching binaries including a compact component. By combining the Gaia DR3 data with radial velocities from the LAMOST spectroscopic survey, we identify three wide binaries possibly containing a compact object. For two of these sources with a main-sequence companion, no obvious excess is observed in the blue/red band of the Gaia DR3 XP spectra, and the LAMOST medium-resolution spectra exhibit clear single-lined features. The absence of an additional component from spectral disentangling analysis further suggests the presence of compact objects within these systems. On the other hand, the visible star of the third source is a stripped giant star. In contrast to most binaries including stripped stars, no emission line is detected in the optical spectra. The unseen star could potentially be a massive white dwarf or neutron star, but the possibility of an F-type dwarf star scenario cannot be ruled out. An examination of about 10 binaries containing white dwarfs or neutron stars using both kinematic and chemical methods suggests most of these systems are located in the thin disk of the Milky Way.